(untitled) (Medical Forum Monthly, 2024)
Objective: The purpose of the hospital-based study was to assess visual impairment in diabetes patients and the factors that may predict it. Study Design: Cross-sectional descriptive study Place and Duration of Study: This study was conducted at the Mehboob Charity Vision International Eye and General Hospital, Mansehra, Pakistan from May 2023 to March 2024 in affiliation with Lincoln University Malaysia, Methods: A study in Pakistan aimed to identify predictors of visual impairment in individuals with type 2 diabetes mellitus (T2DM). The study involved 505 diabetic patients from Mehboob Charity Vision International Eye and General Hospital, Mansehra. Data on socio-demographic, behavioral, and clinical-related variables were collected through structured interviews and clinical examinations. Results: The results showed that visual impairment was prevalent in more than 75% of respondents, with mild and moderate VI being the most common. Older age was a significant predictor, with the odds of having mild and moderate VI increasing with age. Additional variables were found to be predictive, including the length of diabetes, high blood pressure, and inadequate glycemic management. The study suggests more research with larger sample sizes and longitudinal designs and highlights the significance of early detection and therapy of visual impairment in T2DM patients. The present research of 500 diagnosed type 2 diabetes in Pakistan to examine the factors that contribute to visual impairment. More than three quarters of respondents had visual loss with mild to moderate losses being most prevalent. Diabetes duration of more than 10 years, poor glycemic control and hypertension showed strong correlation with visual impairment. Conclusion: These findings suggest tremendous public health importance to call for timely diagnosis, appropriate treatment, and control to prevent DR.